2023
DOI: 10.3390/antibiotics12081248
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance, Genetic Lineages, and Biofilm Formation in Pseudomonas aeruginosa Isolated from Human Infections: An Emerging One Health Concern

Adriana Silva,
Vanessa Silva,
María López
et al.

Abstract: Pseudomonas aeruginosa (PA) is a leading nosocomial pathogen and has great versatility due to a complex interplay between antimicrobial resistance and virulence factors. PA has also turned into one the most relevant model organisms for the study of biofilm-associated infections. The objective of the study focused on analyzing the antimicrobial susceptibility, resistance genes, virulence factors, and biofilm formation ability of thirty-two isolates of PA. PA isolates were characterized by the following analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Additionally, a significant association between antimicrobial resistance and biofilm production has been identified. This correlation is attributed to the extracellular polymeric substances (EPS) produced in biofilms, which impede the entry of antibiotics into the bacterial cells (16). Consistent with our findings, a four-year study in the United States from 2012 to 2015 by Sader et al revealed that the only antimicrobial agents with a sensitivity rate exceeding 90% were associated with CAZ (17).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, a significant association between antimicrobial resistance and biofilm production has been identified. This correlation is attributed to the extracellular polymeric substances (EPS) produced in biofilms, which impede the entry of antibiotics into the bacterial cells (16). Consistent with our findings, a four-year study in the United States from 2012 to 2015 by Sader et al revealed that the only antimicrobial agents with a sensitivity rate exceeding 90% were associated with CAZ (17).…”
Section: Discussionsupporting
confidence: 90%
“…Biofilm formation also increases ATBR in this bacterium. Data indicate a correlation between the occurrence of MDR bacteria, biofilm formation and the expression of virulence, underlining the role of P. aeruginosa as a key model in the study of biofilm-related ATBR (Eladawy et al 2021 , Gajdács et al 2021 , Silva et al 2023 ).…”
Section: Antibiotic Resistance: a Worldwide Threatmentioning
confidence: 99%
“…The high associated mortality of P. aeruginosa can be attributed to several factors, including the frequent occurrence of diverse antibiotic resistance mechanisms, its ability to produce biofilm [6], its association with certain virulence factors [7], and its ability to persist in hospital and natural environments [8]. This is particularly noteworthy in high-risk clones (HRCs), a term often used to refer to multidrug-resistant or extensively drug-resistant P. aeruginosa clones with wide distribution, usually associated with epidemic outbreaks, and exemplified by ST235, ST111, ST233, ST244, ST357, ST308, ST175, ST277, ST654, and ST298 [7].…”
Section: Introductionmentioning
confidence: 99%